Limited diagnostic capacities of two commercial assays for the detection of Leptospira immunoglobulin M antibodies in Laos. - Blacksell, S; Smythe, L; Phetsouvanh, R; Dohnt, M; Hartskeerl, R; Symonds, M; Slack, A; Vongsouvath, M; Davong, V; Lattana, O; Phongmany, S; Keolouangkot, V; et al. (2006)
The diagnostic utility of immunochromatographic (Leptotek) and enzyme-linked immunosorbent assay (ELISA; Panbio) tests for the detection of Leptospira immunoglobulin M antibodies was assessed in febrile adults admitted in Vientiane, Laos. Both tests demonstrated poor diagnostic accuracy using admission serum (Leptotek sensitivity of 47.3% and specificity of 75.5%: ELISA sensitivity of 60.9% and specificity of 65.6%) compared to the Leptospira "gold standard" microscopic agglutination test.